Prevalence of Therapeutic use of Opioids in Chronic non-Cancer Pain Patients and Associated Factors: A Systematic Review and Meta-Analysis - De Sola, Helena; Dueñas, María; Salazar, Alejandro; Ortega-Jiménez, Patricia; Failde, Inmaculada (Frontiers in Pharmacology, 2020)
Objectives: To determine the prevalence and factors associated with the use of opioids among patients with Cchronic Nnon-Ccancer Ppain (CNCP). Methods: A systematic review and meta-analysis. Comprehensive literature searches in Medline-PubMed, Embase and SCOPUS databases. Original studiespapers published between 2009 and 2019 with a cross-sectional design were included. The quality of the studies was assessed with Critical Appraisal Checklist for Studies Reporting Prevalence Data from the Joanna Briggs Institute. Protocol registered in the International Prospective Register of Systematic Reviews (PROSPERO) with reference number: CRD42019137990 Results: Out of the 1310 potential studiesarticles found, 25 studies fulfilled the inclusion criteria. Most of the studies were ofhad a high quality. High levels of heterogeneity were found in the included studies included. In the general population, the prevalence of long-term opioid use was 2.3% (95%CI:1.5%-3.6%), the prevalence of short-term opioid use was 8.1% (95%CI:5.6%-11.6%), and among people with chronic low back pain it was 5.8% (95% CI:0.5% - 45.5%). The prevalence of opioid use among patients from the health records or medical surveys was 41% (95%CI:23.3%-61.3%). Finally, in patients with musculoskeletal pain, the prevalence was 20.5% (95%CI:12.9%-30.9%) and in patients with fibromyalgia, 24.5% (95%CI:22.9%-26.2%). A higher prevalence of opioid use was observed among men, younger people, patients receiving prescriptions of different types of drugs, smokers and patients without insurance or with noncommercial insurance. In addition, non-white and Asian patients were less likely to receive opioids than non-Hispanic white patients. Conclusions: The prevalence of opioid use among patients with CNCP was higher in subjects with short or occasional use compared to those with long- term use. Men, younger people, more chronic pain conditions, and patients without insurance or with noncommercial insurance were most related to opioids use. However, non-white and Asian patients, and those treated by a physician trained in complementary medicine were less likely to use opioids.